3(3x-2)=10-0.5(x+3.5)35(x-2)-15(5x-6)=(22x-63)-21(3x-4)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:22:55
3(3x-2)=10-0.5(x+3.5)35(x-2)-15(5x-6)=(22x-63)-21(3x-4)
3(3x-2)=10-0.5(x+3.5)
35(x-2)-15(5x-6)=(22x-63)-21(3x-4)
3(3x-2)=10-0.5(x+3.5)35(x-2)-15(5x-6)=(22x-63)-21(3x-4)
3(3x-2)=10-0.5(x+3.5)
9x-6 =10-0.5x-1.75
9x+0.5x=10-1.75+6
9.5x=14.25
x=1.5
35x-70-75x+90=22X-63-63X+84
35X-75X-22X+63X=-63+84+70-90
-40x-22x+63x=21+70-90
-62x+63x=91-90
x=1
(1)9x-6=10-0.5x-1.75
19/2x=57/4
x=3/2
(2)35x-70-75x+90=22x-63-63x+84
-35x-75x-22x+63x=84-63+70-90
x=1
3(3x-2)=10-0.5(x+3.5)
9x-6 =10-0.5x-1.75
解 9x+0.5x=10-1.75+6
9.5x=14.25
x=1.5
35x-70-75x+90=22X-63-63X+84
解35X-75X-22X+63X=-63+84+70-90
-40x-22x+63x=21+70-90
-62x+63x=91-90
x=1
第一道过程9x-6=10-0.5x-1.75
9x+0.5x=10-1.75+6
9.5x=14.25
x=1.5
第二道过程35x-70-75x+90=22x-63-63x+84
35X-75X-22X+63X=-63+84+70-90...
全部展开
第一道过程9x-6=10-0.5x-1.75
9x+0.5x=10-1.75+6
9.5x=14.25
x=1.5
第二道过程35x-70-75x+90=22x-63-63x+84
35X-75X-22X+63X=-63+84+70-90
-40x-22x+63x=21+70-90
-62x+63x=91-90
x=1
收起